2019
DOI: 10.32861/jssr.53.830.837
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Behavioral Factors that Cause Student Academic Fraud

Abstract: This study aims to examine a number of behavioral factors from students committing academic fraud in university. The subject of this research is the factors that motivate students to commit academic fraud. The Fraud Pentagon Theory and Gone Theory are used. Behavioral factors include arrogance, pressure, opportunity, rationalization, competence, greed, need, and exposure. The population in this study was the undergraduate students in the Accounting Study Program in the Faculty of Economics and Business at Sura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 0 publications
0
20
3
2
Order By: Relevance
“…However, there are also studies that do not support the opinion that pressure can influence academic fraud, i.e. Artani (2018) and Sasongko et al (2019) who suggest that the element of pressure do not influence academic fraud behavior due to the low level of competition to obtain high grades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also studies that do not support the opinion that pressure can influence academic fraud, i.e. Artani (2018) and Sasongko et al (2019) who suggest that the element of pressure do not influence academic fraud behavior due to the low level of competition to obtain high grades.…”
Section: Introductionmentioning
confidence: 99%
“…This opportunity to commit academic frauds emerges due to the low supervision paid to students. It is also due to the lack of disciplinary action to fraud behavior which will eventually give a deterrent effect to the culprit (Yendrawati & Akbar, 2019;Sasongko et al, 2019). Catacutan's (2019) explained that students commit frauds due to the weak institutional factor in checking for academic fraud.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the supervisor does not monitor the examination well, and he/she does not provide a severe action to students who caught cheating. However, Sasongko et al (2019) found that the other upersonality features that is greed, competence, rationalisation, pressure, exposure and need does not affect student academic fraud.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Literature have discovered various issues concerning the increased frequency of academic dishonesty (Sasongko et al, 2019;Murdiansyah, 2017;McCabe and Drinn, 1999). According to Rakovski and Levy (2007), many researches have researched the students' ethics in higher education.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation